Courage strength wisdom - A first nations community's post-secondary experience. - LePage, Kenneth Federick (Author); Madak, Paul (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2014)
This thesis is about a number of First Nations community members that pursued a post-secondary education. The purpose of the research was to investigate their post-secondary educational experience including motivating factors and importance of the process in their lives and the community they represent. The researcher used a qualitative methodology for the study in the form of focus groups. A traditional talking circle method was used to collect data. Three talking circles took place on-reserve and two questions were asked. Sixteen community members that attended post-secondary education participated. They received emotional support and encouragement from a visionary Sister, peers, family and community members. All the participants spoke of how difficult it was to pursue post-secondary and their fulfilling experience. The participants have found meaningful employment on and off-reserve impacting their community culturally and academically. All of them are playing a vital role encouraging others in their communities to further their education. --Leaf 3. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1947305